Handbook on array processing and sensor networks - Haykin, Simon S. 1931-; Liu, K. J. Ray 1961- (Wiley ;, 2009)
A handbook on recent advancements and the state of the art in array processing and sensor Networks. Handbook on Array Processing and Sensor Networks provides readers with a collection of tutorial articles contributed by world-renowned experts on recent advancements and the state of the art in array processing and sensor networks. Focusing on fundamental principles as well as applications, the handbook provides exhaustive coverage of: wavelets; spatial spectrum estimation; MIMO radio propagation; robustness issues in sensor array processing; wireless communications and sensing in multi-path env.
Includes bibliographical references and index. - Title page (viewed Mar. 26, 2010)
Keywords: Sensor networks; Antenna arrays; Array processors; Réseaux de capteurs; Antennes-réseaux; Processeurs de tableaux; TECHNOLOGY & ENGINEERING; Telecommunications; Sensor-Array; Réseaux de capteurs (technologie); Antennes (électronique); Traitement du signal; Techniques numériques